Experimental study on the tensile response of post‐installed adhesive anchor connections in reinforced and plain concrete beams. (6th December 2021) - Sartipi, Sahand; Emrani, Seyed Mohammad Reza; Epackachi, Siamak; Erfani, Saeed
Abstract: Post‐installed connections are widely used in the rehabilitation, strengthening, and expansion of existing concrete structures. These connections accommodate the connecting of new elements to old concrete using post‐installed anchoring techniques. Attachment of new segments to concrete beams and columns requires the installation of anchors in slim concrete components. Under this condition, the behavior of connection is severely affected by the small width of concrete elements. Additionally, the behavior of anchors is influenced by the confining effects of stirrups in reinforced concrete elements. In this paper, the tensile behavior of chemical anchor connections in single and group formations of four and six anchors is investigated using the results of 36 individual experiments of adhesive anchors installed in plain and reinforced concrete beams. The key design parameters are embedment depth, section width, and effects of the reinforcement. The results indicate high levels of interaction between all studied parameters. The tensile capacities of the single and groups of anchors are compared against ACI 318 predictions. The main effects of parameters, as well as their interactions, are analyzed and discussed. Based on the test results, several recommendations are provided for the installation of adhesive bonded anchors in narrow concrete components.